2015
DOI: 10.1371/journal.pone.0142386
|View full text |Cite
|
Sign up to set email alerts
|

Cinnamic Acid Bornyl Ester Derivatives from Valeriana wallichii Exhibit Antileishmanial In Vivo Activity in Leishmania major-Infected BALB/c Mice

Abstract: Human leishmaniasis covers a broad spectrum of clinical manifestations ranging from self-healing cutaneous leishmaniasis to severe and lethal visceral leishmaniasis caused among other species by Leishmania major or Leishmania donovani, respectively. Some drug candidates are in clinical trials to substitute current therapies, which are facing emerging drug-resistance accompanied with serious side effects. Here, two cinnamic acid bornyl ester derivatives (1 and 2) were assessed for their antileishmanial activity… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(21 citation statements)
references
References 53 publications
0
21
0
Order By: Relevance
“…The first one could be related with the inhibition of the enzymatic systems of the protozoan by blocking the utilization of iron by the parasite, a mode of action which was observed for the African species [46]. The second one could be related with the loss of mitochondrial transmembrane potential [47].…”
Section: Biological Activitiesmentioning
confidence: 97%
“…The first one could be related with the inhibition of the enzymatic systems of the protozoan by blocking the utilization of iron by the parasite, a mode of action which was observed for the African species [46]. The second one could be related with the loss of mitochondrial transmembrane potential [47].…”
Section: Biological Activitiesmentioning
confidence: 97%
“…Therefore, this work conveyed the disclosure of CAD as inhibitors of the new permeability pathways (NPP) induced by Plasmodium in erythrocytes to enable the translocation of carbohydrates and amino acids [46][47][48][49]. Following this pioneering discovery, other authors have proposed different CA-inspired compounds as potential therapeutic agents against malaria [26,28,29], as well as other parasitic diseases [50][51][52]. In view of this, reports have emerged over the past decade where conjugation to CA was proposed as a useful strategy for the rescuing of known antimalarials [53][54][55].…”
Section: Cinnamic Acid Conjugation In the Rescuing Of Classical Antimmentioning
confidence: 99%
“…Recently, Schurigt et al. reported that cinnamic acid bornyl ester from Valeriana wallichi exhibits in vivo antileishmanial activity . Inspired by these reports, here we have synthesized a series of nitro compounds containing m ‐nitrocinnamic acid, α‐aminoisobutyric acid (Aib) and L‐leucine.…”
Section: Introductionmentioning
confidence: 99%